INTEGRATION OF ARTIFICIAL INTELLIGENCE (AI) AND DIGITAL TECHNOLOGY IN ENHANCING 21ST CENTURY SKILLS - Marda’is; Yeni, Dede; Nugraha, Yudi; Tarwana, Wawan; Ochtora, Danesty; Safitri, Vivi Hariyanti; Christiana, Zubaidah; Damayanti, Fitri (Journal of Learning on History and Social Sciences, 2025)
Objective: This literature review aims to analyze and synthesize findings from 21 scholarly journals on the integration of digital technology and Artificial Intelligence (AI) in education to enhance 21st-century skills, such as critical thinking, collaboration, and digital literacy. Method: A Systematic Literature Review (SLR) approach was used to identify research issues, methodologies, and key outcomes from studies focusing on AI, digitalization, and student skill development. Results: The synthesis reveals that AI and digital technologies play a significant role in personalizing learning through adaptive systems and Deep Learning, improving Higher-Order Thinking Skills (HOTS), including creativity and mathematical reasoning, and enabling holistic adaptive assessments encompassing cognitive, affective, and psychomotor domains. Novelty: The review emphasizes AI literacy as a fundamental skill and the need for teacher development in utilizing AI platforms. It concludes that the strategic integration of AI and digital technologies, supported by a constructivist framework and curriculum integration, is crucial in producing graduates prepared for the challenges of the 21st century and Society 5.0.